A comparison of the playing structure in elite kids tennis on two different scaled courts - Bayer, D.; Ebert, M.; Leser, R. (International Journal of Performance Analysis in Sport, 2017)
Available research analysing the playing structure in kids tennis on different scaled courts identifies a severe problem at the transition from the U9 (Orange stage) to the U10 (Green stage), which can mainly be reasoned by the enlargement of the court from a small-sided field to the full-sized court. Aware of this problem, an intermediate stage, called Lime Court (stage), between Orange and Green was introduced in Austria. The study at hand aims to compare the playing structure between the Green and the Lime Court in kids` tennis aged 9-10 years (U10). Twelve videos from matches on Lime in 2013 were analysed and compared to the results found in 2014. The playing structure was defined by 18 performance parameters. The differences in the mean values as well as one-way ANOVA were calculated between the groups. The results found in the study lead to the conclusion that the Lime Court enables children to play more similar to elite players than the Green Court. Thus, Lime closes the existing gap between the Tennis10s stage Orange and Green and should be used for 10-year old tennis players in order to properly develop their playing skills.